1995
DOI: 10.1017/s0043174500080838
|View full text |Cite
|
Sign up to set email alerts
|

Plant Movement and Seed Dispersal of Russian Thistle (Salsola iberica)

Abstract: Russian thistle plant movement and seed dispersal were studied in 1991 and 1992 by placing Russian thistle plants in the center of wheat fields in eastern Washington. Three adjacent site treatments, with 24 plants on each site, were used each year; wheat stubble, summerfallow planted to winter wheat, and a “stationary” site. Plants in the “stationary” site were anchored to the ground to prevent tumbling. Plants in the stubble and summerfallow sites were allowed to tumble naturally. Individual plant movement wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 9 publications
(25 reference statements)
2
39
0
Order By: Relevance
“…Salsola tragus plants are characterized by high seed production, i.e. over 50 000 seeds per plant, and the ability to spread seed widely due to tumbling at plant maturity …”
Section: Introductionmentioning
confidence: 99%
“…Salsola tragus plants are characterized by high seed production, i.e. over 50 000 seeds per plant, and the ability to spread seed widely due to tumbling at plant maturity …”
Section: Introductionmentioning
confidence: 99%
“…This indicates that S. australis plants moved and shed seed in a manner similar to that for S. iberica or S. kali (Young, 1991; Mallory‐Smith et al. , 1993; Stallings et al. , 1995).…”
Section: Discussionmentioning
confidence: 93%
“…Species of the Salsola genus that are agricultural weeds are often early successional species that engage in broad scale seed dispersal (Schmidt & Reeves, 1989; Mallory‐Smith et al. , 1993; Stallings et al. , 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since resistance to ALS inhibitors can be spread both by seed and pollen, once the initial incident of resistance occurs, the resistant subpopulation will dominate the population in a very short period of time. Stallings et al (1995a) studied the Russian thistle plant movement and seed dispersal in order to follow the spread of chlorsulfuron-resistant biotypes. They found that 48% to 68% of the Russian thistle seed were lost as the plants tumbled across the fields, and they were carried by varying winds from 60m to more than 4 km.…”
Section: Genetics Mechanisms and Spread Of Als Resistancementioning
confidence: 99%